2016
DOI: 10.1093/humrep/dew272
|View full text |Cite
|
Sign up to set email alerts
|

Preconception use of pain-relievers and time-to-pregnancy: a prospective cohort study

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Currently, pregnant women are advised against nonsteroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen and naproxen because studies have associated first-trimester use with increased risk for miscarriage (Nakhai-Pour et al, 2011) and cardiac malformations (Ericson and K€ all en, 2001) and third-trimester use with premature closure of the ductus arteriosus (Koren et al, 2006), renal impairment (Bennett et al, 1996), and other adverse health effects in childhood (Nezvalova-Henriksen et al, 2013. Further, use during the peri-conceptual period is associated with reduced female fecundity (McInerney et al, 2017). Similarly, most pregnant women are advised against using high doses of aspirin, or using aspirin for extended periods (James et al, 2008;Rumack et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pregnant women are advised against nonsteroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen and naproxen because studies have associated first-trimester use with increased risk for miscarriage (Nakhai-Pour et al, 2011) and cardiac malformations (Ericson and K€ all en, 2001) and third-trimester use with premature closure of the ductus arteriosus (Koren et al, 2006), renal impairment (Bennett et al, 1996), and other adverse health effects in childhood (Nezvalova-Henriksen et al, 2013. Further, use during the peri-conceptual period is associated with reduced female fecundity (McInerney et al, 2017). Similarly, most pregnant women are advised against using high doses of aspirin, or using aspirin for extended periods (James et al, 2008;Rumack et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Research on multiple species has shown adverse effects of aspirin and indomethacin on ovulation through prostaglandin disruption (Sirois et al, 2004). Pre-conception consumption of NSAID's has also been associated with effects on implantation and reduced female fecundability (Mcinerney et al, 2017); however, peri-implantation use of aspirin was associated with increased fecundability (Jukic et al, 2020). Other findings in female adults include analgesic-induced disruption of menstruation and ovulation (Meyboom et al, 1995;Salman et al, 2015).…”
Section: Reproductive Defectsmentioning
confidence: 99%
“…In another study, it was reported that glutathione concentration decreased in the fetal mouse liver without any malformation due to the paracetamol application to the mice between the 6th and 13th days of their pregnancy [21]. Oxidative stress stimulates the formation of mitochondrial peroxynitritis, which triggers mitochondrial DNA damage, and hepatic macrophages advance liver damage from paracetamol [2].…”
Section: Discussionmentioning
confidence: 97%
“…P aracetamol has been widely used worldwide since its release in the mid-1950s due to its painrelieving and antipyretic effects [1]. Nonsteroidal anti-inflammatory drugs are frequently used among pregnant women, preferred for its availability to be purchased without a prescription [2]. Paracetamol is a pain reliever that is widely used due to its reliability, cheapness and effectiveness [3].…”
Section: Introductionmentioning
confidence: 99%